The study of the structure of anxiety in athletes - Y. A. Statsenko; H. .. Wardi; I. V. Glebova; M. A. Sarkisyan; A. G. Ponomareva; I. A. Charikova; D. N. Cvirko; L. A. Kalinkin; L. V. Kutniakhova; T. A. Dotsenko; M. E. Biandzetskaya (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the structure of disorders caused by anxiety in athletes. Materials and methods: the objects of the first task of the research were different terminological definitions and classifications of anxiety disorders. Comparative analysis of the definitions and concepts used in psychology, physiology, sports medicine, theory and methodology of physical education has been carried out. The second task was to determine the leading factors characterizing the psychological status of athletes, and to give them the descriptive characteristics. A factor analysis was conducted on the results of testing 79 athletes of combat sports (34 men, 45 women) using the M Luscher color test and the integrative anxiety test by AP Bizyuk, LI Wasserman, BV Iovlev. Results: Luscher's test scores (total deviation from the autogenous rate, mental performance, vegetative coefficient) explained only 14.5% of the total variance. Simultaneously, the indicator of situational anxiety from Luscher's test was not included in any factor. The informativeness of more detailed integrative anxiety test was significantly higher: its indicators were included in 3 factors, explaining totally 49.5% of the total variance, as well as in the general factor, which explains 33% of the total variance. Conclusions: the emotional component (emotions which cause situational anxiety) contributes largely to the total anxiety level, some smaller contribution accounts for the social components (fear of condemnation, dependence on the opinions of others), finally, the personal anxiety contributes to it even less.